PENDISTRIBUSIAN ZAKAT PRODUKTIF DALAM PERSPEKTIF ISLAM - Siti Zalikha (Islam Futura, 2016)
The obligation on charity and explanation of the law has been emphasized since the days of Mecca,the strongest opinion in the second year Hijr. However, the occurrence of major changes in the world that followed the revolution of science, technology, political and economic structure, made the concept of wealth and poverty is changing dramatically in which legal paradigm is no longer sufficient to carry out the teachings of charity in society. Hence, it is needed the criticism and evaluation of understanding and perception of charity, both on theoretical concepts and operational concepts, as well as implementation and application models. This study discuss the criticism to rebuild the whole concept of charity, comprehensive and precise with a variety of related concepts, including the concept of property and ownership, economy and fairness in various dimensions.